STRES KERJA PERAWAT DIRUANG RAWAT INAP RSUD H. A. SULTHAN DAENG RADJA KABUPATEN BULUKUMBA - Nur Awaliyah Hasbi; Fatmawati; Nadia Alfira (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2019)
Stress is a physical and psychological reaction to environmental demands on a person. Nurse work stress is a condition of the results of an individual's subjective appreciation which can be in the form of interactions between individuals and the work environment that can threaten and stress psychologically, physiologically and nurses' behavior. According to a survey from the 2015 PPNI (Indonesian National Nurses Association), 51% of nurses experienced stress at work, were tired, were not friendly, often had dizziness, lack of rest due to high workload and inadequate income. If this is left unchecked it will certainly have a worse impact. From the results of a preliminary study conducted by researchers, the number of nurses in the inpatient room is 171 nurses spread in several rooms. The purpose of this study was to determine the description of the work stress of nurses in the inpatient hospital of H. A. Sulthan Dg Radja Bulukumba Regency. This research uses descriptive design with cross sectional survey approach. The population in this study was 171 people. The sample in this study were 95 people with a sampling method using probability sampling method with sampling techniques using proportional stratified random sampling. The results of the study found that nurses work stress levels were most at mild stress levels of 54 respondents (56.8%), while moderate stress levels were 41 respondents (43.2%). The conclusion of this study is nurses in the inpatient hospital H. A. Sulthan Dg Radja Bulukumba Regency in 2018 shows that the majority of nurses tend to experience work stress at a mild level of 84 respondents (88.4%). It is recommended for health workers, especially nurses to need to do effective stress management in the form of relaxation techniques, time management, good problem solving and so on.